DIGITAL MEDIA REVIEWS. - Cardell, Vic (Notes, 2002)
Evaluates several web sites related to music in the U.S. Content and style of the web sites containing databases of American sheet music; Elements of the selected sheet music databases of images; Digitization of the sheet music databases with images.